Digital approach for lip prints analysis in Malaysian Malay population (Klang Valley): scanning technique - Noor Hazfalinda Hamzah; Umi Kalsom Jamaludin; Khairul Osman; Gina Francesca Gabriel (Penerbit Universiti Kebangsaan Malaysia, 2021)
Lip print is useful in forensic investigations for individual identification. The present study aimed to discriminate sex based on lip print patterns in Malaysian Malay population in Klang Valley using a scanning technique. Lip prints of 360 subjects (180 males and 180 females) were taken using the lipstick-cellophane tape technique, pasted onto A4 papers. These papers were then scanned using Brother DCP-J100 printer (300dpi resolution). The images were analysed using a software based on Suzuki and Tsuchihashi’s classification. The lip print images were divided into six sections which are upper left, upper middle, upper right, lower right, lower middle and lower left. The Pearson chi-square test showed that there are significant differences (p < 0.05) between sexes in each section except for the upper middle section. In males, type V (irregular pattern) was the dominant pattern for upper left, upper right, lower right and lower left sections (ranging from 71.1% to 86.7%) while type IV (reticular pattern) was dominant at upper and middle sections (ranging from 57.2% to 66.1%). Type IV (48.3%) was dominant in upper middle section for female, while for the rest of the sections, type V was the dominant lip print pattern (ranging from 40% to 82.8%). These results showed that sex differentiation between males and females in Malaysian Malay population, Klang Valley can be suggested to be used for identification in forensic investigation.